PFM.36 Arabin Pessary to Prevent Spontaneous Preterm Birth: Experience of a Specialist Preterm Labour Clinic. (9th June 2014) - Care, A; Sharp, A; Alfirevic, Z
Abstract : Background: Arabin pessary remains a controversial but potential candidate to prevent sPTB in high risk asymptomatic patients. One large randomised controlled trial has promised hope, demonstrating staggering results that, as yet, have not been replicated. It is cheaper than both cervical cerclage and progesterone, can be fitted in the clinic and reduces concerns regarding patient compliance. Our aim was to analyse our outcomes and experience with all patients treated with Arabin pessary in Liverpool Preterm Labour (PTL) Clinic. Method: Data was collected on 38 singleton patients with a history of sPTB (n = 11), PPROM (n = 7) or significant cervical surgery (n = 12) who were identified with a short cervix on TVUSS. Results: The median cervical length at insertion was 17mm, with median GA 19wks (IQR 7). Rates of sPTB were 25% (sPTB), 29% (PPROM) and 25% (cervical surgery). Reported side effects were minimal but included increased discharge, discomfort with pessary on insertion and awareness of pessary. One pessary fell out. The median gestation at delivery was 37weeks (IQR 6). Additional or concomitant therapy (progesterone/cerclage) was used in 7 cases, this occurred less frequently with increasing clinician confidence in pessary. Conclusion: Arabin pessary is cheap, easy to insert and well tolerated by women but not universally suitable due to one pessary falling out. We currently offer this method as first line for prevention of sPTB in high-risk women as no difference in PTB rates as been found when compared to previous use of progesterone. Further evidence is required to compare effectiveness against other treatments.